Penerapan Metode Sosiodrama Dalam Keterampilan Berbicara Siswa Kelas IV Pada Pembelajaran Bahasa Indonesia Di MI Muhammadiyah Sinduraja - Hidayah, Nur; BS, Abdul Wachid; Ningsih, Tutuk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Students' speaking skills always require practice and also the right encouragement by the teacher. This is where the teacher as a person who has maturity in thinking should build a replication of activities and learning in the classroom as needed by students. This research is an action study of classroom action. The subjects of this study were fifth grade students at MI Muhammadiyah Sinduraja. The sociodrama method was carried out, the researchers obtained data on the percentage of good progress to improve students' speaking skills. The percentage which was originally shown at 60% had an increase to 75% when the action test was carried out in the second cycle.